Dynamic Allocation of Mobile Units in Disaster Support: A Case Study of the Noto Earthquake - Tsuchiya, Shin (Proceedings of the International ISCRAM Conference, 2026)
This study analyzes how mobile units were used during the 2024 Noto Peninsula Earthquake and clarifies how needs changed over time and what information management issues arose. Field investigations in Suzu City and Shika Town show that demand for mobile toilets, laundry units, and residential trailers shifted as the recovery process progressed. In several cases, mismatches between unit specifications and evacuee composition reduced effectiveness. Existing disaster information systems are largely sector-based and designed around fixed facilities, making it difficult to coordinate mobile resources in response to changing conditions. To address this gap, this study proposes a two-layer information management model that links individual-level data with mobile unit data through aggregated indicators. The proposed Dynamic Unit Allocation Framework provides a foundation for managing mobile disaster support more effectively.